INTERSTITIAL LUNG DISEASES IN CHILDREN - Nuritdinova Gavkhar Taipovna; Soliyeva Mavlyuda Odiljonovna (Scholar Express Journals, 2022)
There is an undoubted link between chronic lung diseases in children and adults. This is a single clinical problem for pediatricians and therapists, it has not only medical, but also social significance. Chronic respiratory diseases that began in childhood often lead to disability of patients in adulthood, and sometimes to dramatic outcomes.
Keywords: Lung Angiomatosis; Fibrosis; Bronchiectasis; Pulmonary